El-ahwat : a fortified site of the early iron age near Nahal 'Iron, Israel. (Culture and History of the Ancient Near East, 2009)
The excavations at el-Ahwat constitute a unique and fascinating archaeological undertaking. The site is the location of a fortified city dated to the early Iron Age (ca. 1220-1150 BCE), hidden in a dense Mediterranean forest in central Israel, near the historic 'Arunah pass. Discovered in 1992 and excavated between 1993 and 2000, the digs revealed an urban "time capsule" erected and inhabited during a short period of time (60-70 years), with no earlier site below or subsequent one above it. This report provides a vivid picture of the site, its buildings, and environmental economy as evinced by the stone artifacts, animal bones, agricultural installations, and iron forge that were uncovered here. The excavators of this site suggest in this work that the settlement was inhabited by the Shardana Sea-Peoples, who arrived in the ancient Near East at the end of the 13th century BCE and settled in northern Canaan. In weighing the physical evidence and the logic of the interpretation presented herein, the reader will be treated to a new and compelling archaeological and historical challenge. "...this final publication of el-Ahwat will hold great value for those studying settlement, architecture, and change in the hill country culture of Iron Age Canaan." Jeff Emanuel